DESENTRALISASI PENGAMBILAN KEPUTUSAN DAN PENERIMAAN IMPLEMENTASI SISTEM IMFORMASI KEUANGAN DAERAH (SIKD) DI KOTA/KABUPATEN BEKASI - Sabaruddinsah Sabaruddinsah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2011)
This study examines influence decentralization of decision making toward implementation Government Financial Information System (SIKD) to test of the influence of implementation Government Financial Information System (SIKD) toward performance officer and satisfaction officer as intervening and moderating variable.This research represents the empirical test which used convenience sampling techniques in data collection. Data were collected from 10 officers for each 6 of Bekasi. Data analysis uses Structural Equation Model (SEM) with the program Plural Least Square (PLS).Result of hypothesis examination indicates that seven hypothesis are given but which are accepted five hypothesis and two hypothesis is only refused. Accepted hypothesis 1 there are positive influence between decentralization of decision making to adoption officer and significant. Accepted hypothesis 2 there are positive influence between decentralization of decision making to implementation Government Financial Information System (SIKD) and significant. Accepted hypothesis 3 there are adoption officer to implementation Government Financial Information System (SIKD) and significant. Accepted hypothesis 5 there are decentralization of decision making to design SIKD and significant. Accepted hypothesis 6 there are negative influence between decentralization of decision making to implementation Government Financial Information System (SIKD) that is mediated by adoption officer which adoption officer is moderating variable and significant. Refused hypothesis 4 there are positive influence between design SIKD to implementation Government Financial Information System (SIKD) but not significant. And Refused hypothesis 7 there are negative influence between decentralization of decision making to implementation Government Financial Information System (SIKD) that is mediated by design SIKD which design SIKD is not moderating variable and also not significant.